Effect of pulmonary rehabilitation program on patients admitted to ICU:a comparative cross sectional study - Fadaii, Abbas; Bagheri, Bahador; Pirsalehi, Ali; Taherkhanchi, Bahar; Abbasi, Mohammad Amin (Archives of Advances in Biosciences, 2015)
Generally ICU patients are in critical status and need long stay in ICU. Pulmonary rehabilitation program (PRP) is considered as an important tool to improve outcome and shorten the length of stay in ICU. The aim of this study was to investigate whether PRP can affect outcome and duration of hospitalization in ICU patients. This study was performed in medical ICU of Labafi Nejad hospital, Tehran, Iran during 2012 and 2013. All of patients who had more than one day stay in ICU were included in the study. They underwent PRP. We compared length of stay, mortality rate and number of hospitalized patients within 2 years in patients with PRP and patients without PRP. In 2012, 155 patients and in 2013, 173 patients were admitted in ICU. Admission period was 15 ± 2.7 and 11 ± 2.1 days, respectively (p< 0.001). Pulmonary physiotherapy showed no effect on patients’ outcome in which during 2012, 94 patients were discharged and 61 patients were died and in 2013, 98 patients were discharged and 64 patients were died (p=0.9). Our study shows that PRP can shorten hospitalization time which can indirectly decrease hospitalization costs but there is no effect on overall survival.